MR Imaging of Ankle Arthroplasty Implants: Findings of Normal and Symptomatic Patients. Issue 3 (11th September 2017) - de Cesar Netto, Cesar; Schon, Lew; Da Fonseca, Lucas Furtado; Maccario, Camilla; Chinanuvathana, Apisan; Fritz, Jan
Category: Ankle Introduction/Purpose: Metal artifact reduction magnetic resonance imaging (MRI) of the ankle allows for comprehensive imaging evaluation of pain and dysfunction after arthroplasty including periprosthetic bone resorption and osteolysis, synovitis, infection, periprosthetic fractures, arthrofibrosis and component malalignment. The aim of this study was to show the appearance of normal ankle arthroplasties and common pathologies using optimal imaging parameters including newer multispectral MR techniques such as MAVRIC and SEMAC. Methods: We included adult 20 asymptomatic volunteers (12 men and 20 women, mean age of 62.41 years (range, 42-74 years), mean body mass index (BMI) of 29.02 kg/m2 (range, 20.30-41.15 kg/m2), average postoperative time of 13.84 months (range, 3-29 months)) and 12 symptomatic patients (12 men and 20 women, mean age of 62.41 years (range, 42-74 years), BMI of 29.02 kg/m2 (range, 20.30-41.15 kg/m2) and an average postoperative time of 13.84 months (range, 3-29 months)) with total ankle replacement that agreed to cooperate and signed a written informed consent. The MRI exams of asymptomatic volunteers were obtained for research purposes only, whereas the clinical and MRI exams of asymptomatic volunteers were obtained for research and clinical purposes. Images were assessed by two different readers. Results: The following key pathophysiologic issues were assessed regarding imaging findings: Normal MRI appearances and MRI diagnosis of complications: Implant integration: Biological and cement fixation, fibrous membrane formation, bone resorption and osteolysis Bone: progressive osteoporosis, implant subsidence, osseous stress reaction and focal overload, fracture, osteonecrosis Synovium: non-specific synovitis, wear-induced synovitis, infection, arthrofibrosis Impingement syndromes Sagittal implant alignment Musculotendinous abnormalities Neurovascular compromise Types and frequency of modes of failure of ankle arthroplasty. Conclusion: Ankle arthroplasties can be evaluated using metal artifact reduction MRI by optimizing the imaging protocol. Newer imaging sequences can provide optimal diagnostic value with shorter acquisition time and better metal artifact reduction using commercially available MR scanners. These imaging characteristics and scan techniques can provide optimal diagnostic value for patients with ankle arthroplasties, improving patient care.